2011
DOI: 10.1128/ec.05163-11
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Growth of Saccharomyces cerevisiae through Iron Chelation

Abstract: Curcumin, a polyphenol derived from turmeric, is an ancient therapeutic used in India for centuries to treat a wide array of ailments. Interest in curcumin has increased recently, with ongoing clinical trials exploring curcumin as an anticancer therapy and as a protectant against neurodegenerative diseases. In vitro, curcumin chelates metal ions. However, although diverse physiological effects have been documented for this compound, curcumin's mechanism of action on mammalian cells remains unclear. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…For example, CDC1, mutants of which arrest at G 1 , encodes a Mn 2+ -dependent protein (Supek et al 1997). Iron chelation by curcumin treatment inhibits cell cycle progression at G 1 (Minear et al 2011). Ca 2+ regulates the onset of mitosis through the calcium-dependent phosphatase calcineurin and Mpk1p, a component of the MAPK pathway (Mizunuma et al 1998).…”
Section: Ion Homeostasismentioning
confidence: 97%
“…For example, CDC1, mutants of which arrest at G 1 , encodes a Mn 2+ -dependent protein (Supek et al 1997). Iron chelation by curcumin treatment inhibits cell cycle progression at G 1 (Minear et al 2011). Ca 2+ regulates the onset of mitosis through the calcium-dependent phosphatase calcineurin and Mpk1p, a component of the MAPK pathway (Mizunuma et al 1998).…”
Section: Ion Homeostasismentioning
confidence: 97%
“…8). 41-47 The metal chelating activity of the β-diketo moiety is independent of oxidative transformation. It may be disturbed by the formation of the cyclopentadione ring which is more nucleophilic (acidic) than the β-diketo moiety of curcumin.…”
Section: Putting Metabolism Autoxidation and Biological Activity Tomentioning
confidence: 99%
“…36) Minear et al reported that curcumin significantly decreased intracellular iron levels. 38) Thus, our results suggested that curcumin entered the cells and protected against SNP-induced cytotoxicity by its free radical-scavenging and iron-chelating abilities.…”
Section: Discussionmentioning
confidence: 77%